2021
DOI: 10.5194/fr-24-395-2021
|View full text |Cite
|
Sign up to set email alerts
|

Albian to Turonian agglutinated foraminiferal assemblages of the Lower Saxony Cretaceous sub-basins – implications for sequence stratigraphy and paleoenvironmental interpretation

Abstract: Abstract. Albian to Turonian carbonate deposits at three different locations of the Lower Saxony Cretaceous and thereby of the European mid-Cretaceous epeiric shelf sea were investigated for their fossil agglutinated foraminiferal fauna. In this study, 71 samples from two quarries and three drill cores were treated with formic acid, which enabled the study of agglutinated foraminiferal assemblages even in highly lithified limestones. In total, 114 species were determined and classified as belonging to nine mor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 89 publications
4
7
0
Order By: Relevance
“…This species was previously reported to range from the Santonian to Eocene (Kaminski and Gradstein, 2005;Kaminski et al, 2011). This study extends the range of A. glabratus, while Besen et al (2021) already observed the species in the Cenomanian to Turonian from the Lower Saxony Basin. A. glabratus indicates bathyal settings (Kaminski and Gradstein, 2005).…”
Section: Ammoanitasupporting
confidence: 82%
See 3 more Smart Citations
“…This species was previously reported to range from the Santonian to Eocene (Kaminski and Gradstein, 2005;Kaminski et al, 2011). This study extends the range of A. glabratus, while Besen et al (2021) already observed the species in the Cenomanian to Turonian from the Lower Saxony Basin. A. glabratus indicates bathyal settings (Kaminski and Gradstein, 2005).…”
Section: Ammoanitasupporting
confidence: 82%
“…3). Thus, recorded assemblages can be assigned to the mid-latitude shelf biofacies proposed by Besen et al (2021). The consistent occurrence of all morphogroups and the recorded diversities (Fig.…”
Section: Salzgitter-saldersupporting
confidence: 61%
See 2 more Smart Citations
“…It is worth mentioning, that the genus Arenobulimina Cushman, 1927 is included in the suborder Ataxophragmiina Fursenko, 1958 displaying a "wall…(roughly, coarsely)…agglutinated typically with calcareous cement" (= non-canaliculate) (Kaminski, 2014, p. 102). Moreover, the genus Arenobulimina is recorded mostly from shales, as an inhabitant of open marine, deep water environments, contrary to the new taxon described herein (e.g., Reuss, 1845;Cushman, 1927;Gawor-Biedowa, 1969;Barnard & Banner, 1980;Frieg & Price, 1982;Hart et al, 1989;Besen et al, 2021). Hence, in accordance with the taxonomic relevance of a pseudokeriotheca as discussed previously, a new genus is introduced herein as Siphopfenderina gen. nov. with the new combination Siphopfenderina geyikensis (Solak, 2022).…”
Section: Introductionsupporting
confidence: 58%